High Local Variability in Hard Coral Juveniles Reveals Uneven Recovery Potential Across Proximate Islands in Karimunjawa, Indonesia - Muhammad Fadhilah Ramadhan; Dwi Haryanti; Yoko Nozawa; Diah Permata Wijayanti; Agus Sabdono; Yopi Novita (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2026)
Coral reefs are vital marine ecosystems in the Karimunjawa Archipelago, Indonesia, but they face increasing threats from climate change and local anthropogenic stressors. Coral juveniles are widely recognized as reliable indicators of recent recruitment and reef recovery potential. In 2023, hard coral (scleractinian) juveniles (<10 cm in diameter) and benthic assemblages were surveyed at nine islands in this archipelago. At each island, 50 photo quadrats (50 × 50 cm), placed at 1 m intervals along a 50 m transect at a depth of ~ 7 m, were analyzed. The statistical approach zero-inflated Generalized Linear Mixed Model (GLMM) with AIC model selection was used to determine the factors influencing the abundance of hard coral juveniles. The highest coral juvenile density is on Sambangan Island (145 juveniles; 11.6 colonies.m-2), and the lowest is on Tengah Island (19 juveniles; 1.5 colonies.m-2). Most juveniles belonged to Montipora (49%), Fungia (20%), and Porites (6%). Hard corals dominated the benthic cover, with median island-level values ranging from 25% to 79%. Juvenile densities varied greatly among islands, with a significant positive correlation between juvenile density and hard coral cover detected at only two islands. Overall, juvenile density declined with proximity to the main Karimunjawa Island, the center of human activity. Our findings revealed unexpectedly high spatial variation in coral juvenile abundance among proximate islands, indicating differences in recovery potential and anthropogenic pressure. Our results highlight the need for island-specific coral reef conservation strategies, even across short spatial scales.